Does ipsilateral and bilateral knee strength status predict lower extremity injuries of elite judokas; a prospective cohort study - Darbandi, S. M.; Hosseinzadeh, M.; Zarei, M.; Behm, D. G. (Research in Sports Medicine, 2024)
The association of pre-participation knee muscle strength status with lower limb injury occurrence was investigated. Knee extensors and flexors muscle strength status including the traditional hamstrings/quadriceps (H/Q), Q/Q, H/H, and the non-dominant H/Q: dominant H/Q, HQ:HQ, ratios were recorded before the 10 month judo activity. Fifteen lower limb sport injuries were recorded for 53 judokas during the follow-up questionnaires. Significant accuracy of dominant H/Q ratio 60º/s (AUC 0.702, 95% CI 0.520 to .883, p = 0.023), as well as HQ:HQ ratios 300º/s (AUC .318, 95% CI 0.138 to 0.497, p = 0.040), and 60 º/s (AUC 0.311, 95% CI 0.130 to 0.491, p = .033) were revealed discriminating between injured and uninjured judokas. The optimum cut-off of dominant H/Q ratio associated with belonging to uninjured judokas group was 43.2% (sensitivity, 0.974; specificity, 0.533). Isokinetic knee muscle dynamometry is useful for predicting the likelihood of lower limb injuries in professional judokas during competitive activity.